Evaluation of postoperative lung volume and perfusion changes by dual-energy computed tomography in patients with lung cancer. Issue 90 (May 2017) - Choe, Jooae; Lee, Sang Min; Chae, Eun Jin; Lee, Sang Min; Kim, Yong-Hee; Kim, Namkug; Seo, Joon Beom
Highlights: Postoperative volume compensation predominantly occurred in the ipsilateral lobe. Postoperative blood volume similarly increased in both lungs. The modified method was comparable for prediction of postoperative lung function. Abstract: Purpose: The aim of our study was to retrospectively evaluate postoperative physiologic changes in lung cancer patients using dual-energy CT (DECT), and develop modified methods reflecting postoperative change for predicting pulmonary function. Methods and materials: 88 patients (M:F = 64:24; mean age, 63.5 years) with lung cancer who underwent DECT and pulmonary function tests before and after operation were included. Volume and iodine values for perfusion of each lobe were quantified. The predicted postoperative FEV1 using the current method was calculated by multiplying the preoperative FEV1 by the fractional contribution of perfusion of the remaining lung. The modified method reflecting postoperative volume change was compared to the current method. Results: Postoperative lung volume showed compensatory increases in the contralateral and remaining ipsilateral lobes, with a significantly greater increase in the ipsilateral lobe than contralateral lobe (21.8% ± 46.2% vs. 10.0% ± 20.8%, P = 0.031). Perfusion analysis showed blood volume increases in both ipsilateral and contralateral lobes without statistical differences (blood volume ratio difference, 29.2% ± 26.7 vs. 24.6% ± 16.5, P = 0.368). The performance of the modified method considering postoperative lung volume change was comparable to that of the current method in the development and validation datasets (95% CI, −24.5% to 37.1% vs. −33.3% to 22.2% and −23.6% to 32.0% vs. −31.9% to 16.0%, respectively). Conclusions: Postoperative compensatory increases in lung volume and perfusion occur in different ways. Our modified method incorporating postoperative lung volume changes can be considered a comparable method for prediction of postoperative lung function.